2012
DOI: 10.1210/jc.2012-1364
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Procedural Tight Glycemic Control during Early Percutaneous Coronary Intervention Is Associated with a Lower Rate of In-Stent Restenosis in Patients with Acute ST-Elevation Myocardial Infarction

Abstract: In hyperglycemic patients with STEMI, optimal peri-procedural glycemic control by reducing oxidative stress and inflammation may improve the outcome after PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 33 publications
4
72
0
Order By: Relevance
“…Marfella et al [18] indicated that tight glycemic control might have anti-inflammatory and antiremodeling effects during AMI. Finally, tight glycemic control may reduce the rate of in-stent restenosis in patients with STEMI who underwent PCI [19]. Thus, for patients with STEMI, intensive insulin therapy should be applied to ameliorate the detrimental effects because of stress hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Marfella et al [18] indicated that tight glycemic control might have anti-inflammatory and antiremodeling effects during AMI. Finally, tight glycemic control may reduce the rate of in-stent restenosis in patients with STEMI who underwent PCI [19]. Thus, for patients with STEMI, intensive insulin therapy should be applied to ameliorate the detrimental effects because of stress hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of persistent hyperglycemia after AMI, only a few studies have reported its effect on clinical outcomes [23][24][25]. Poor serum glycemic control after ischemic insults is common in patients with diabetes because some of the physiologic responses differ from those without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have examined postprocedural serum glucose levels for short periods ranging from 24 h to 4 days, and observed MACE at 1 or 6 months [23,24,27]. In contrast to previous studies, we followed patients for 12 months and used FU-HbA1c instead of glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple trials attempting to demonstrate a benefit with glucose-insulin-potassium infusions have yielded conflicting results, possibly due to the failure to reach target glucose levels in the treatment arm. Finally, a recent study by Marefella et al, demonstrated optimal peri-procedural glycemic control in the setting of ST-segment elevation MI to reduce oxidative stress, inflammation, and in-stent restenosis on 6-month follow-up coronary angiogram (20). While these trials were all conducted in patients with acute MI, the benefits of glycemic control may extend to the almost 35% of patients that go on to develop peri-procedural myonecrosis and possibly even more so those with clinically significant peri-procedural MI.…”
Section: Discussionmentioning
confidence: 99%